Ulema in the period of Stalinist and Bolshevik Repressions in Kazakhstan: the fate of Aliyasqar Aytqozhauly - Shapoval, Yu.; Lipina, T.; Bekbolat, A. (Eurasian Journal of Religious Studies, 2023)
The article is devoted to the analysis of the biography of the representative of Kazakh  ulemas during the period of  the Soviet authority repressions in Kazakhstan. The consequences of the repression were a physical destruction of a large group of local Muslim leaders, a great damage to Islamic education, as well as to the functioning of Muslim communities in Kazakhstan as a whole. The purpose of this article is to show repressions against ulemas through the fate of Aliyasqar Aytqozhauly as an alim from Kokshetau, whose name was included in the “Biographies of the Islamic Scholars of Our Times” by Sadwaqas Ghilmani. As a methodological basis, the authors  applied the micro-historical approach and the biographical method, allowing to study the repressive policy of the Soviet state in 1920s-1930s through the prism of people's lives and micro-events and, accordingly, “ to hear the voice of Muslims” themselves, who experienced the pressure of the repressive machine. In order to present a coherent and whole view of the events, the article shows the activity of the different actors, particularly Muslim clergy representing different projects of development of Islam and Islamic education, the Central Spiritual Directorate of Muslims of Inner Russia and Siberia (SSAM), which coordinated work of clergy in most Kazakhstani regions, the Soviet state and its repressive bodies such as the USPA/NCIA. The source base of the study includes information about the alim in the “Biographies of the Islamic Scholars of Our Times” by Sadwaqas Ghilmani as well as archival materials. The reconstruction of biographies of local ulema in Kazakhstan, the actualization of their names and activities, is an important contribution to the process of their full rehabilitation, as well as to overcoming "white spots" and gaps in the history of Islam, the restoration of the historical process continuum and its comprehension.Key words: Islam, ulama, the Soviet state, repressive policy, rehabilitation.
Keywords: Islam; Ulama; the Soviet Union; repressive policy; rehabilitation